Employees' personality preferences and their impact on the relationship between leadership styles and organisational commitment - Sahraee, Rezvan; Abdullah, Haslinda (Universiti Putra Malaysia Press, 2018)
This research investigates whether personality traits influence employees' preferences for different styles of leadership and whether the congruence between the leadership style that employees prefer and the leadership style that they actually perceive can moderate the effects of a leader's leadership style on organisational commitment. Personality traits were measured using the NEO Five-Factor Inventory (Costa & McCrae, 1992), organisational commitment with a scale developed by Meyer and Allen (1997), and leadership styles using the Leadership Assessment Inventory (Burke, 1994). This cross-sectional study involved 312 employees from an automotive company in Tehran, Iran. The results indicate that individuals with extraversion and openness to experience personality traits tend to prefer the transformational leadership style, while those with conscientiousness and neuroticism personality traits prefer the transactional leadership style although no association was found for agreeableness. Moreover, it is found that the congruence between the leadership style which employees prefer and the leadership style they actually perceive moderates the effects of the leadership style on affective commitment.